Cognitive functioning after repetitive transcranial magnetic stimulation in patients with cerebrovascular disease without dementia: a pilot study of seven patients - Rektorova, I; Megova, S; Bares, M; Rektor, I (Journal of the neurological sciences, 2005)
AIMS: Examine whether one session of high frequency repetitive transcranial magnetic stimulation (rTMS) applied over the left dorsolateral prefrontal cortex (DLPFC) would induce any measurable cognitive changes in patients with cerebrovascular disease and mild cognitive deficits. PATIENTS AND METHOD: Seven patients with cerebrovascular disease and mild executive dysfunction entered the randomised, controlled, blinded study with a crossover design. rTMS was applied either over the left DLPFC (an active stimulation site) or over the left motor cortex (MC; a control stimulation site) in one session. Each patient participated in both stimulation sessions (days 1 and 4) and the order of stimulation sites (DLPFC or MC) was randomised. A short battery of neuropsychological tests was performed by a blinded psychologist prior to and after each rTMS session. Psychomotor speed, executive function, and memory were evaluated. RESULTS: The only mild but significant stimulation site-specific effect of rTMS was observed in the Stroop interference results (i.e. improvement) after the stimulation of DLPFC but not MC in comparison with the baseline scores (Wilcoxon, Z=-2.03, p=0.04). Patients improved in the digit symbols subtest of the Wechsler adult intelligence scale-revised after both rTMS sessions regardless of the stimulation site (DLPFC or MC; Z=-2.06, p=0.04 and Z=-2.06, p=0.04, respectively). There was no measurable effect of rTMS in any other neuropsychological test. CONCLUSION: Our pilot study results showed that one session of the high frequency rTMS applied over the left DLPFC was safe in patients with cerebrovascular disease and mild executive deficits, and may induce measurable positive effects on executive functioning.
Keywords: Cerebrovascular Disorders; Female; klinické křížové studie; Psychomotor Performance; Neuropsychological Tests; Wechsler Scales; ženské pohlaví; neuropsychologické testy; lidé; psychomotorický výkon; dvojitá slepá metoda; Motor Cortex; Electromagnetic Fields; Pilot Projects; Memory; pilotní projekty; Cross-Over Studies; prefrontální mozková kůra; kognice; Double-Blind Method; Male; Aged; psychiatrické posuzovací škály; motorické korové centrum; elektromagnetická pole; Cognition; cerebrovaskulární poruchy; paměť; senioři; mužské pohlaví; Prefrontal Cortex; Psychiatric Status Rating Scales; Wechslerovy škály; Humans